6=x+y; x≥0; y≥0
x^2 * y^2 -наибольшее
x^2 *y^2=x^2 *(6-x)^2
f(x)=x^2(6-x)^2; x∈[0;6]
f'(x)=2x *(6-x)^2 +2(6-x) *(6-x)' *x^2=(6-x)*( 2x(6-x) -2)=(6-x)(-2x^2+12x-2)
f'(x)=0; (6-x)(-2x^2+12x-2)=0
6-x=0 ili -2x^2+12x-2=0
x=6 x^2-6x+1=0; D/4=3^2-1=8=(2√2)^2
x1=3-2√2; x2=3+2√2
f(0)=0^2 *(6-0)^2=0
f(6)=6^2 *(6-6)^2=0
f(3-2√2)=(3-2√2)^2 * (6-3+2√2)^2=(17-12√2) *(9+12√2+8)=(17-12√2)(17+
+12√2)=17^2 -(12√2)^2=289-288=1; -наибольшее
f(3+2√2)=(3+2√2)^2 * (6-3-2√2)^2=
=(17+12√2)((3-2√2)^2(17+12√2)*(17-12√2)= 17^2-144*2=1-наибольшее
3-2√2 и 3+2√2- два неотрицательных слагаемых